Immunohistochemical analysis of p16 expression, HPV infection and its prognostic utility in oral squamous cell carcinoma. (31st May 2013) - Gröbe, Alexander; Hanken, Henning; Kluwe, Lan; Schöllchen, Maximilian; Tribius, Silke; Pohlenz, Philipp; Clauditz, Till; Grob, Tobias; Simon, Ronald; Sauter, Guido; Heiland, Max; Blessmann, Marco
<x xml:space="preserve">Abstract</x> Objectives Functional inactivation of p16 is an early and frequent event in the carcinogenesis of tumours of the head and neck region. However, the prognostic relevance of p16 protein expression for these tumours has been controversial. This study aims to examine immunohistochemical expression of p16 and HP virus in a large number of oral carcinomas, and possible correlation with clinical features of the tumours and survival of the patients. Methods Two tissue microarrays composed of 222 oral carcinomas and 427 squamous cell carcinomas of the head and neck region were used for this study. Sections were stained immunohistochemically (anti‐p16), and PCR analysis (HPV status) was carried out. Correlation of p16 expression/HPV status with features of tumours and with survival of the patients was analysed by means of Chi‐squared test and using Kaplan–Meier analysis, respectively. Results p16 expression was found immunohistochemically in 74% of tumours, but was not significantly correlated with features of the tumours, but recurrence‐free survival of the patients (P = 0.009) if located predominantly nuclear. On the other hand neither intensity of p16 expression (P = 0.41) nor HPV status (P = 0.82) had any effect on these two aspects. Conclusion Immunohistochemical expression of p16 alone provides a limited tool for diagnosis and prognosis of carcinomas of the head and neck region. Immunohistochemical analysis of p16 depending on its intracellular location might serve as a surrogate marker for HPV infection.